Aluminato de lantânio puro e dopado: obtenção e caracterização elétrica - Villas-Bôas, Lúcia Adriana (Universidade Federal de São Carlos, 2009)
In the attempt to find new electrolyte materials for Solid Oxide Fuel Cells (SOFC) that works at low temperature, perovskite-type materials have been intensively investigated. These materials have favorable crystal structure for the creation of oxygen vacancies since a variety of elements can be accommodate in the crystal lattice. Among these materials stands out LaAlO3-based perovskite which, when adequately doped, presents considerable ionic conductivity. However, in spite of doped LaAlO3 presents high ionic conductivity, it also presents p-type electronic conductivity under oxidizing conditions, which would limit his use as electrolyte. In this work, powders of pure LaAlO3 and Sr, Ca and Ba-doped individually and, in the case of Sr, also Pr and Mn-co-doped, were prepared by oxide mixture through successive calcinations. Samples, obtained via isostatic pressing, were sintered at 1500 and 1600 °C in air during 6 h of soaking time. Sintered samples were characterized by X-ray diffraction, scanning electron microscopy and impedance spectroscopy. Among the different kind of dopants (Ca, Ba and Sr), the Sr-doped sample was that one which had the higher conductivity, both the grain (σgrain = 1,8x10-2 S/cm at 800 °C) and total (σtotal = 9,3x10-3 S/cm at 800 °C) conductivity. Sr- and Pr-doped samples presented higher ionic conductivity than Pr-undoped samples (σtotal = 2,3x10-2 S/cm at 800 °C). This increase was attributed to the highest oxygen vacancy mobility since the presence of Pr+3 in crystal lattice did not introduce additional oxygen vacancies. The Mn co-doping generated samples with high electronic conductivity. It was also observed that all of the samples presented two common features: the total conductivity is controlled by the grain boundary, i. e., the grain boundary is more resistive than the grain, and the microstructures are two-phase and the majority phase is dopant depend.
Pure and doped lanthanum aluminate: obtaining and electrical characterization
Keywords: Cerâmica eletrônica; Célula a combustível; Condutividade elétrica; Eletrólito sólido; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA